Facteurs de protection ayant contribué à la résilience scolaire de bacheliers vivant avec un trouble développemental du langage - Tardif, Suzie; Dumoulin, Catherine; Bergeron, Geneviève (Canadian Journal of Education/Revue canadienne de l'éducation, 2026)
The article discusses the protective factors that contributed to the academic resilience of four Quebec high school graduates living with a developmental language disorder. A multiple-case study was conducted based on individual life story interviews, supported by artifacts. The results show that school, family, and peers had a positive influence in coping with language and academic difficulties, isolation and bullying, health issues, and the distrust of certain support staff members, as well as challenges related to school organization.